Students and Learning - Richard Ruopp (Journal of Research in Rural Education, 1993)
As my colleagues and I said in our overview of the LabNetwork above, ''Telecommunication for teacher enhancement, such as that explored in the LabNet project, is unique among so-called 'new educational technologies,' in that it affects what happens in the classroom indirectly. . .. This particular kind of telecommunication is for the teachers first and foremost."